1997
DOI: 10.1123/jtpe.17.1.40
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Accountability on Task Accomplishment in Collegiate Football

Abstract: An A-B-A-B withdrawal design was used to evaluate whether accountability, in the form of public posting, was effective in improving football players’ performance in successfully blocking the forward momentum of the defense and in running routes to a criterion at, or greater than, 90% correct. Five wide receivers on a college football team participated in the study. Data were collected during practice sessions and weekly games. The players’ game performance was not intervened on and served as a measure of both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
21
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 8 publications
5
21
1
Order By: Relevance
“…One cannot, with validity, evaluate another' s work without knowing about it. This awareness, which refers to the actual or perceived knowledge that others have regarding one' s performance, is consistent with a study done by Ward, Smith, and Sharpe (1997), which found that athletes performed at higher levels when specific measures were posted publicly. Our results suggest that with regard to job satisfaction and trust, awareness is the most important aspect.…”
Section: Discussionsupporting
confidence: 84%
“…One cannot, with validity, evaluate another' s work without knowing about it. This awareness, which refers to the actual or perceived knowledge that others have regarding one' s performance, is consistent with a study done by Ward, Smith, and Sharpe (1997), which found that athletes performed at higher levels when specific measures were posted publicly. Our results suggest that with regard to job satisfaction and trust, awareness is the most important aspect.…”
Section: Discussionsupporting
confidence: 84%
“…Further, the data in both studies showed that gains in performance generalized from practice to game conditions. Similar results were reported by Ward, Smith, and Sharpe (1997) for blocks and routes completed correctly by five receivers (1997). The movements on the field of three female high school soccer players were improved by providing public posting, goal setting, and oral feedback (Brobst & Ward, 2002).…”
supporting
confidence: 91%
“…The head coach and the lead author established a goal of 90% correct performance of the target behaviors. The criterion was chosen because the skills were already in the repertoire of the players, because the coach believed that her players ought to be demonstrating a proficiency level of at least 90% during scrimmages, and because similar studies had used this criterion (e.g., Ward & Carnes, 2002;Ward, Smith, & Sharpe, 1997). The head coach and lead author met with the 3 participants as a group and explained the target behavior, how it was measured, and the rationale for the 90% criterion.…”
Section: Experimental Design and Proceduresmentioning
confidence: 99%
“…Studies combining public posting and goal setting in sport settings have been used to reduce absenteeism, late arrivals, and early departures as well as to increase the work rate of members of a youth swimming team (McKenzie & Rushall, 1974); to increase the rate of legal body checking in a collegiate ice hockey team (Anderson, Crowell, Doman, & Howard, 1988); to increase the practice and game performance of collegiate football players (Ward & Carnes, 2002;Ward, Smith, & Sharpe, 1997); and to reduce illegal and improper behaviors occurring during tennis matches by collegiate tennis players (Galvan & Ward, 1998).…”
mentioning
confidence: 99%